Analisis Kemampuan Literasi Matematika Siswa Kelas VIII SMP dalam Menyelesaikan Soal-Soal Model PISA - Ni Nyoman Sriningsih; Ketut Sarjana; Laila Hayati; Sudi Prayitno (Griya Journal of Mathematics Education and Application, 2022)
This study aims to determine the mathematical literacy ability of class VIII SMP Negeri 1 Mataram students in solving PISA model questions for the 2020/2021 school year. This type of research is qualitative research. The population in this study were all eighth grade students of SMP Negeri 1 Mataram. The sampling technique used purposive sampling in order to obtain a sample with students ranked 1, 2 and 3. The data collection technique used a mathematical literacy test in the form of descriptions and interviews. The data analysis technique used descriptive analysis and Aiken's V content validity test analysis. The results of this study showed that the mathematical literacy skills of SMP Negeri 1 Mataram students were still relatively low. Furthermore, it is studied based on level, students excel at level 1 with the highest percentage of 100% and less at level 6 with a percentage of 0%.